Canal Water Quality Status in Settlement and Trade Area - Weli Zuandi; Rizki Putranto; Sigit Normagiat (Indonesian Journal of Applied Research (IJAR), 2022)
Decreasing canal water quality due to densely populated settlements and trade is a common problem in urban areas. This study aims to assess the current water quality standards of the Sei Jawi canal so that appropriate management steps can take. Water sampling was divided into seven stations based on the difference in distance from the canal estuary. The parameters measured were Dissolved Oxygen (DO), pH, temperature, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The results of the research on the water quality of the Sei Jawi channel revealed that the parameters of temperature, pH, TDS, and TSS were not below the threshold of the quality standard, while the DO level was in the category III quality standard, but the COD and BOD levels were higher than those outlined in PP No. 22 the year 2021 about the Implementation of Environmental Protection and Management